58 Characterisation of the structural and electrical impact of an atrial septal defect. (16th October 2019) - O'Neill, L; Sim, I; O'Hare, D; Flyod, C; Roney, C; Whitaker, J; Mukherjee, R; Razeghi, O; Niederer, S; Alam, H; Rosenthal, E; Jones, M; et al.
Abstract : Background: Uncorrected atrial septal defects (ASD) are associated with atrial arrhythmias (AAs) however little is known about the bi-atrial arrhythmia substrate in these patients and optimal rhythm management strategies remain unclear. Hypothesis: We hypothesised that the right atrium (RA) is important to atrial arrhythmogenesis in the ASD cohort and that 1) changes of structural and electrical remodelling and 2) arrhythmia triggers/ectopic foci would be present in the RA of ASD patients. Additionally, we hypothesised that atrial remodelling may be reversible with ASD closure and that percutaneous closure may reduce the prevalence of AAs in this cohort. Methods: Comprehensive assessment of atrial arrhythmia substrate was undertaken in unclosed ASD patients and non-congenital heart disease AF control patients. Atrial late gadolinium enhancement cardiac MRI (CMR) was performed prior to ASD closure and bi-atrial fibrosis burden quantified. EP studies were carried out at ASD closure, including bi-atrial voltage mapping, ERP measurement and an isoprenaline infusion with assessment of atrial ectopy. Control patients underwent the same protocol prior to and during AF ablation. Origin of atrial ectopy was also assessed on 24 hour holter monitoring. One year post closure, ASD patients undergo repeat CMR and limited right atrial EP studies Meta-analysis to evaluate the effect of percutaneous ASD closure on the prevalence of AAs is ongoing. Results: CMR Assessment of Arrhythmia Substrate; 36 ASD and 36 control patients underwent bi-atrial CMR imaging prior to procedure. Using an 'image intensity ratio' threshold of 1.2, both RA and LA fibrosis burden were significantly greater in ASD vs control patients (P<0.001 for both) (table 1 ). In ASD patients, fibrosis burden in the RA was significantly greater than in the LA (P=0.010). Fibrosis burden and RA volume were significantly associated with the presence of documented AAs in the ASD cohort (P=0.037 and P=0.005) (figure 1 ). Invasive Electrical Assessment of Arrhythmia Substrate; 18 ASD and 18 control patients underwent EP studies. RA mean voltage was significantly lower and proportion of low voltage (<0.5mV) significantly greater in ASD vs control patients (P=0.01 and P=0.022) (table 1 ). LA low voltage area was greater in ASD patients, but this did not reach significance (P=0.059). Within ASD patients, mean voltage was significantly lower and proportion of low voltage areas significantly greater in the RA vs the LA (P=<0.001 and P=0.003). RA ERP was longer in ASD than control patients at a BCL of 600ms (P=0.021). (Figure 2 ). Assessment of Arrhythmia Triggers ; During isoprenaline infusion right sided ectopy was seen in 71% of ASD patients compared to 69% of controls (P=N/S) and bi-atrial ectopic foci were present in 43% of ASD patients and 31% of controls (P=N/S). On 24-hour holter monitoring right sided ectopy was more prevalent in ASD vs control patients (P=0.038) and ectopic burden was associated with presence of documented AAs in ASD patients (P=0.04). Effects of Closure: Two patients have had repeat CMR post closure (analysis pending). One patient had repeat EP studies 1 year post closure with a visual reduction in low voltage areas in the RA. Results of meta-analysis are pending. Conclusion: This work highlights the bi-atrial nature of the atrial arrhythmia substrate in ASD patients. Further investigation is needed to evaluate the effects of closure on this substrate.